2005
DOI: 10.4102/aveh.v64i1.205
|View full text |Cite
|
Sign up to set email alerts
|

The innovativeself - adjustable Adspecs TM

Abstract: A method of self-refraction, based on an old concept implemented with the aid of modern technology, is spectacles with adjustable lenses. The spectacle design is referred to as the Adspecs TM . The advantage of the Adspecs is that the wearer can adjust the powers of the lenses to suit his or her visual needs. The power is spherical and ranges from −6 to 6 D. Studies were undertaken in Ghana and South Africa. Subjects were instructed under supervision to adjust the powers of the Adspecs as accurately as possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…However, when compared with cycloplegia subjective refraction, the refraction differed for all methods in urban and rural children. This finding is similar to previous studies that also reported differences in refractive outcomes between self-refracting methods and clinical standard of CSR due to mechanical and optical limitations of adjustable glasses 18 23 25–27. The results, however, are contrary to suggestions that children from less socioeconomic background are less likely to accurately perform self-refraction compared with their counterparts from more privileged backgrounds 17.…”
Section: Discussionsupporting
confidence: 86%
“…However, when compared with cycloplegia subjective refraction, the refraction differed for all methods in urban and rural children. This finding is similar to previous studies that also reported differences in refractive outcomes between self-refracting methods and clinical standard of CSR due to mechanical and optical limitations of adjustable glasses 18 23 25–27. The results, however, are contrary to suggestions that children from less socioeconomic background are less likely to accurately perform self-refraction compared with their counterparts from more privileged backgrounds 17.…”
Section: Discussionsupporting
confidence: 86%
“… 9 , 32 Only one study in Ghana looked at the benefit of adjustable spectacles for near vision, although this study only had a small group of 16 participants aged 40+ years. 37 The study found that 6/6 vision was achieved by eleven of the 16 participants (78.6%) with self-adjustable silicone liquid-filled spectacles. 37 …”
Section: Self-adjustable Spectaclesmentioning
confidence: 94%
“… 37 The study found that 6/6 vision was achieved by eleven of the 16 participants (78.6%) with self-adjustable silicone liquid-filled spectacles. 37 …”
Section: Self-adjustable Spectaclesmentioning
confidence: 94%
See 2 more Smart Citations